Konstruksi citra positif perusahaan rokok melalui film bertema batik - Novita Dwi Wulandari; Pratita Rara Raina (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2025)
Indonesia Kaya, initiated by a cigarette company, uploaded a batik-themed film in 2018 on the IndonesiaKaya YouTube account. The author sees indications that there is a construction of a positive image of a cigarette company through the representation presented in the film, so the purpose of this study is to reveal how the positive image of a cigarette company is displayed in a batik-themed film. The research method used is a qualitative method with representation by Stuart Hall as its main analysis tool. The result is a positive image of a cigarette company displayed in a batik-themed film through the representation presented in the film, namely Intentional Representation and Constructionist Representation. The positive image that appears in the scene in the film is that the existence of a cigarette company is no longer in doubt and is a local product that has been attached to the Indonesian nation; the cigarette company has preserved traditional products; the cigarette company has a winding journey story until now it has succeeded; the cigarette company cares about the environment, culture, and the Indonesian nation; inspiration for all cigarette factories; and is used as a role model for other cigarette factories because of its success. In this case, batik is positioned as a commodity that can generate profit for cigarette companies, namely by constructing a positive image of cigarette companies. Not only commodifying batik, but as a product of a media, in the film there is also commodification of content, audience, and labor.